2020
DOI: 10.1016/j.jad.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The psychological burden of the COVID-19 pandemic and associated lockdown measures: Experience from 4000 participants

Abstract: Highlights The COVID-19 pandemic had significant mental health impacts on the population of Kuwait. Unemployment, uncertainty, distress, increasing deaths and lockdown measures contribute to the burden. From our experience risk factors include; female, smoker, past psychiatric history, increased social media use. Availability of psychological support and mental health awareness reduces the burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
113
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(147 citation statements)
references
References 30 publications
(27 reference statements)
13
113
0
13
Order By: Relevance
“…Most of the included studies showed that COVID-19-related emotional reactions such as worry, fear about contracting the virus and stress predicted mental health outcomes in young people such as depression, anxiety, OCD symptoms, somatic symptoms and intensified behaviour problems. This is generally consistent with evidence on the impact of COVID-19 on adult mental health [ 49 , 50 ], yet not surprising. It has been well established in the literature that children, and especially adolescents, are susceptible to experiencing mental health problems, while most mental disorders have their onset in this age period [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Most of the included studies showed that COVID-19-related emotional reactions such as worry, fear about contracting the virus and stress predicted mental health outcomes in young people such as depression, anxiety, OCD symptoms, somatic symptoms and intensified behaviour problems. This is generally consistent with evidence on the impact of COVID-19 on adult mental health [ 49 , 50 ], yet not surprising. It has been well established in the literature that children, and especially adolescents, are susceptible to experiencing mental health problems, while most mental disorders have their onset in this age period [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Increased screen use behaviors may further be problematic, as subgroups of especially vulnerable individuals may be at risk of developing chronic and excessive usage patterns. Previous research showed that such behaviors relate to poorer psychological and physical well-being ( 3 , 15 , 24 , 25 ). Additionally, these behaviors may become addictive over time, so that several researchers argued that addiction-related disorders need special attention during the COVID-19 pandemic ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such excessive screen use behaviors can be associated with negative effects on psychological well-being during COVID-19-related confinements: students were negatively affected in their sleep quality, sleep duration, physical well-being, and mental health by excessive screen time ( 15 ); increased social media use was associated with a greater tendency to be diagnosed with depression or anxiety ( 24 ); finally, more time consuming news led to higher levels of anxiety and stress ( 3 , 25 ). Moreover, individuals during adolescence and young adulthood may be especially vulnerable to develop excessive, impulsive–compulsive screen use behaviors corresponding to the concept of “behavioral addiction” ( 11 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the emotional strain during the pandemic, there is increasing concern about its impact on mental health ( Burhamah et al 2020 ; Planchuelo-Gómez et al, 2020 ). A national survey in China at the initial stage of COVID-19 outbreak indicated that 27.9% of participants had symptoms of depression, and 31.6% had symptoms of anxiety ( Shi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%